New records of thrips species on mango and natural enemies associated - Soares de Matos, Sidneia Terezinha [UNESP]; Andrade, Daniel Junior de [UNESP]; Paneghini Zanata, Renan Moises [UNESP]; Azevedo, Emiliano Brandao de [UNESP]; Bezerra Lima, Elison Fabricio (Soc Brasileira Fruticultura, 2019)
The mango tree (Mangifera indica L.), native to Asia, is expanding in Brazil. However, research related to phytophagous organisms and natural enemies associated with this fruit are scarce in the country. The aim of this work was to report new species of thrips-pest and natural enemies associated with mango tree inflorescence. The work was carried out in a Tommy Atkins mango orchard located in the municipality of Jardinopolis, Sao Paulo, Brazil. The arthropods found in malformed inflorescences were collected and identified. Frankliniella gemina Bagnall, Frankliniella distinguenda Bagnall (Thysanoptera: Thripidae) and Haplothrips gowdeyi (Franklin) (Thysanoptera: Phlaeothripidae) thrips-pest species were recorded for the first time associated with inflorescence in mango orchards. The predators were collected in association with the phytophagous thrips.
Keywords: Thysanoptera; pest; predators